Determination of Phenols in Water by Modified Polymer Extraction-Fluorine Derivative Gas Chromatography-Negative Chemical Ionization Mass Spectrometry - Zhang, Li; Zhang, Chen-Ling; Zhang*, Yong-Tao; Gui, Jian-Ye; Li, Xiao-Ya (Asian Journal of Chemistry, 2014)
A method of phenol extraction by modified styrene-divinylbenzene polymer was established. We introduced fluorine element into phenols to enhance the electronegativity and the analytes were determined by gas chromatography-negative chemical ionization mass spectrometry (GC-NCI-MS), with detection limits lower than 0.10 μg/L. The phenols were extracted among pH 2-4 and eluted by 3 mL acetone and 5 mL dichloromethane; they were derivatized under the conditions of 20 μL K2CO3 (30 %) and 2,4,5,6-pentafluoro-benzyl bromide (5 %); derivative products were purified by 6 mL toluene/hexane (6:1, v/v); analytes were analyzed qualitatively and quantitatively by GC-NCI-MS. The coefficient correlations were all higher than 0.99 and detection limits were in the range of 0.03-0.09 μg/L. The recovery of phenols was between 65 and 94 % with relative standard deviations varied from 5 and 17 %.